Rheological, sensory, and microstructural properties of fresh and frozen/thawed mashed potatoes enriched with different proteins. Issue 1 (1st January 2018) - Miao, Wenhua; Hatab, Shaimaa; Gu, Yiwei; Wang, Lufeng; Xu, Xiaoyun; Pan, Siyi
ABSTRACT: In this study, the effect of the addition of soybean protein isolate (SPI), whey protein isolate (WPI), whole milk powder (WMP), and sodium caseinate (SC) on the rheological, physical, sensory, and structural properties of fresh and frozen/thawed mashed potatoes formulated with added cryoprotectants [kappa-carrageenan (κ-C) and xanthan gum (XG)] was compared. Steady shear flow rate curves indicated a non-Newtonian fluid and exhibited typical shear thinning (pseudoplastic) behavior ( n  < 1) with all added proteins. The results showed that there is no significant change in the apparent viscosity ( η app ) of fresh mashed potatoes (FMP) and frozen/thawed mashed potatoes (F/TMP) with added WMP and SC at a concentration of 5 g/kg. While the addition of SPI at a concentration of 10 g/kg increased the η app and pseudoplasticity, which indicates that the SPI behaves as harder fillers. Based on the sensory evaluation results, WPI and WMP could incorporate to FMP without losing the sensory quality of the product. F/TMP samples with addition of SPI were judged more acceptable than other processed samples, evidencing the ability of this protein to reduce the influence of freeze/thaw process.